EFFECTIVENESS AND SAFETY OF PROPAFENONE (PROPANORM®) AND AMIODARONE (CORDARONE®) IN PATIENTS WITH ATRIAL FIBRILLATION, ARTERIAL HYPERTENSION, CORONARY HEART DISEASE, AND CHRONIC HEART FAILURE WITH INTACT LEFT VENTRICULAR SYSTOLIC FUNCTION - O. N. Miller; S. A. Starichkov; Yu. M. Pozdnyakov; S. A. Luchinsky; A. V. Tarasov; V. L. Doshchitsyn; O. A. Kramynina; E. G. Volkova; D. L. Ilyinykh (Российский кардиологический журнал)
Clinical effectiveness and safety of Propanorm® was studied in patients with arterial hypertension (AH), coronary heart disease (CHD), chronic heart failure (CHF) with intact systolic left ventricular (LV) function, and atrial fibrillation (AF). Effectiveness and safety of Propanorm® was compared to those in Cordarone®. Out of 137 randomised patients, 110 were included in the study (59 in the Propanorm® group, 51 – in the Cordarone® group) and followed up for 12 months. Primary end-points included all-cause mortality, cardiovascular mortality, fatal and non-fatal myocardial infarction and stroke. Secondary end-points included recurrent AF episodes, their duration, AF or decompensation-related hospitalisation rates, systolic and diastolic LF function dynamics during the treatment, and safety profile of Propanorm® and Cordarone® in CHF with intact systolic LF function. The treatment of the main pathology was associated with achieving target blood pressure (BP) levels in 67,3% of the patients, reduction in functional classes (FC) of angina (70%) and CHF (94,5%), and decrease in cardiac decompensation-related hospitalisation rates by 72,9%. After 6 and 12 months of the therapy, Propanorm® effectiveness was as high as 67,4% and 52,9%, respectively, being similar to that for Cordarone® (62,7% and 52,9%, respectively). In 33,9% of the patients, Propanorm® therapy was associated with a reduction in clinical AF symptoms, their duration, ventricular rate during AF paroxysm, and increased number of asymptomatic AF episodes by 30,9%. In cardiac patients, Propanorm® was safer than Cordarone®, with respective incidence of adverse effects of 0% vs. 31,6%. The study PROSTOR is being continued, and the present paper describes the results of 12-month therapy.